Speech intelligibility of English spoken by Indonesian and Taiwanese speakers and judged by Taiwanese listeners: application of TOCS+ automatic software - Windiahsari Windiahsari; Li-Mei Chen (Journal on English as a Foreign Language, 2023)
Former investigations were about the familiarity advantage that people with the same language backgrounds are more intelligible. Besides, particular English was most intelligible to participants with high certain English familiarity. This study investigated how Taiwanese listeners judge the English speech intelligibility of Taiwanese and Indonesian speakers. Thirty Indonesian speakers and thirty Taiwanese speakers participated in this study. Ninety Taiwanese listeners were recruited to judge speech intelligibility. The recording and judging process used the TOCS+ software (Hodge et al., 2009). The software provided 124 contrast items of minimal pairs for the recognition task, including contrast of syllable shape, vowels, and consonants. The listeners' judgments were then analyzed by the TOCS+ software automatically. It was found that Taiwanese English speaker is more intelligible to Taiwanese listeners. The variables that predict intelligibility for Indonesian speakers are syllable shape contrast item correct (SSIC) and consonant item correct (CIC), while Taiwanese speakers’ SSIC and vowel item correct (VIC) did not predict intelligibility. Only CIC predicts intelligibility. Both groups made similar errors in consonant voicing. The study's findings contribute to the teaching materials for the English preparation of students who will study abroad.